Bimbingan Teknis Penyusunan Rencana Kerja Anggaran dan Belanja Koperasi Bagi Aparatur Sipil Negara (ASN) Kementrian Koperasi dan Usaha Kecil Menengah - Elya Dasuki, Rima (E-Coops-Day, 2024)
The Cooperative Budget and Expenditure Plan (RAPBK) is an important instrument for risk control, strategic planning and financial management. The aim and objective of this technical guidance is so that participants can prepare and implement the RAPBK properly and correctly, because the preparation and implementation of a good RABK is very important for the success and sustainability of cooperatives so that they can ensure cooperative operations run efficiently, increase transparency, and achieve their long-term goals better. effective. The method of providing technical guidance for preparing RAPBK for ASN of the Ministry of Cooperatives and SMEs is through various steps, namely planning activities, coordinating interested parties, preparing teaching materials, implementing and supervising technical guidance so that it is in accordance with planning. Transparency and accountability ensure that cooperative financial management is open and responsible. Transparency allows members to access relevant information and understand how cooperative funds are used, while accountability ensures that administrators are responsible for managing funds and implementing budget plans in accordance with member mandates. Building trust, ensuring good financial management, and maintaining company sustainability depend on these two principles.